Winding core, solid-state battery, battery pack, and vehicle
Patent Information
- Application Number
- CN202511276620.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-08
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2045-09-08
AI Technical Summary
但固态电池的电极材料在充放电的过程中,会出现体积的膨胀,进而容易造成电极材料出现裂纹甚至粉化,从而破坏电极材料与集流体的接触性,使得活性材料从极片上脱离,引起电池容量的快速衰减
[0030] In the scheme disclosed herein, the main component of the first flat section includes an oxide solid electrolyte, which thus possesses high mechanical strength and a low expansion rate during charge and discharge, thereby reducing the capacity decay rate of the solid-state battery. The main component of the second flat section includes at least one of a sulfide solid electrolyte and a halide solid electrolyte, which can possess high ionic conductivity. Therefore, the flat section formed by stacking multiple first flat sections and multiple second flat sections can improve the battery capacity of the solid-state battery and reduce the capacity decay rate of the solid-state battery.
Smart Images

Figure CN121192273B_ABST
Abstract
Description
Technical Field
[0001] This disclosure relates to the field of battery technology, and in particular to a winding core, a solid-state battery, a battery pack, and a vehicle. Background Technology
[0002] Solid-state batteries, compared to liquid batteries, use a solid electrolyte membrane instead of a separator and electrolyte liquid, resulting in higher safety and energy density. However, during charging and discharging, the electrode materials in solid-state batteries expand in volume, which can easily cause cracks or even pulverization of the electrode materials. This can disrupt the contact between the electrode materials and the current collector, causing the active material to detach from the electrode and leading to a rapid decrease in battery capacity. Summary of the Invention
[0003] Therefore, this disclosure provides a winding core, a solid-state battery, a battery pack, and a vehicle, which can reduce the rate of capacity degradation of solid-state batteries. The technical solution is as follows:
[0004] In a first aspect, a core is provided, the core being obtained by winding laminated sheets and including a straight portion and two curled portions located on both sides of the straight portion;
[0005] The laminated sheet includes multiple first straight segments, multiple second straight segments, and multiple curled segments;
[0006] Multiple first straight segments and multiple second straight segments are alternately connected with multiple curled segments along the winding direction of the laminated sheet. After the laminated sheet is wound, multiple first straight segments and multiple second straight segments are stacked together to form the straight portion, and multiple curled segments are respectively curled and stacked on one side of the straight portion to form the curled portion.
[0007] At least a portion of the main components of the first flat segment includes an oxide solid electrolyte;
[0008] At least a portion of the main components of the second flat segment include at least one of sulfide solid electrolyte and halide solid electrolyte.
[0009] In some possible implementations, after the laminated sheet is wound, a plurality of first straight segments and a plurality of second straight segments are alternately stacked together to form the straight portion.
[0010] In some possible implementations, the main components of the coiled segment include at least one of a sulfide solid electrolyte and a polymer solid electrolyte.
[0011] In some possible implementations, the laminate is obtained by stacking a first electrode sheet and a composite sheet, wherein the composite sheet is obtained by stacking two solid electrolyte layers and a second electrode sheet located between the two solid electrolyte layers;
[0012] The first electrode sheet includes a first current collector and a first active material layer coated on both sides of the first current collector;
[0013] The main component of the first active material layer located in the first straight section includes an oxide solid electrolyte, and the main component of the first active material layer located in the second straight section includes at least one of a sulfide solid electrolyte and a halide solid electrolyte.
[0014] After the laminated sheet is wound, the areal density of the first active material layer located in the curled portion is 30%-100% of the areal density of the first active material layer located in the straight portion;
[0015] Preferably, after the laminated sheet is wound, the areal density of the first active material layer located in the curled portion is 40%-85% of the areal density of the first active material layer located in the straight portion.
[0016] In some possible implementations, after the laminated sheets are wound, the areal density of the solid electrolyte layer in the flat portion is 1 mg / cm³. 2 -20mg / cm 2 ;
[0017] When the areal density of the solid electrolyte layer located in the flat portion is less than or equal to 5 mg / cm³ 2 At that time, the areal density of the solid electrolyte layer located in the curled portion is 60%-95% of the areal density of the solid electrolyte layer located in the straight portion;
[0018] When the areal density of the solid electrolyte layer located in the flat portion is greater than 5 mg / cm³ 2 At that time, the areal density of the solid electrolyte layer located in the curled portion is 10%-95% of the areal density of the solid electrolyte layer located in the straight portion;
[0019] Preferably, the areal density of the solid electrolyte layer located in the flat portion is less than or equal to 5 mg / cm³. 2 At that time, the areal density of the solid electrolyte layer located in the curled portion is 65%-85% of the areal density of the solid electrolyte layer located in the straight portion;
[0020] When the areal density of the solid electrolyte layer located in the flat portion is greater than 5 mg / cm³ 2 At that time, the areal density of the solid electrolyte layer located in the curled portion is 20%-70% of the areal density of the solid electrolyte layer located in the straight portion.
[0021] In a second aspect, a solid-state battery is provided, the solid-state battery comprising the core described in any of the first aspects.
[0022] In some possible implementations, the solid-state battery further includes a plastic casing that encloses the core.
[0023] In some possible implementations, the solid-state battery further includes a rigid housing that encloses the wound core;
[0024] Preferably, the rigid housing includes an annular frame and two sidewalls;
[0025] The annular frame surrounds the core, and the annular frame is made of nickel-plated steel.
[0026] The two sidewalls are located on both sides of the core along the stacking direction of the straight portion of the core, and the outer edges of the two sidewalls are connected to the annular frame. The sidewalls are made of aluminum.
[0027] Preferably, when the solid-state battery further includes a plastic casing, the rigid casing encloses the plastic casing.
[0028] Thirdly, a battery pack is provided, the battery pack comprising any of the battery packs described in the second aspect.
[0029] Fourthly, a vehicle is provided, the vehicle including the battery pack described in the third aspect.
[0030] In the scheme disclosed herein, the main component of the first flat section includes an oxide solid electrolyte, which thus possesses high mechanical strength and a low expansion rate during charge and discharge, thereby reducing the capacity decay rate of the solid-state battery. The main component of the second flat section includes at least one of a sulfide solid electrolyte and a halide solid electrolyte, which can possess high ionic conductivity. Therefore, the flat section formed by stacking multiple first flat sections and multiple second flat sections can improve the battery capacity of the solid-state battery and reduce the capacity decay rate of the solid-state battery. Attached Figure Description
[0031] To more clearly illustrate the technical solutions in the embodiments of this disclosure, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of this disclosure. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0032] Figure 1 This is a schematic diagram of the structure of a winding core provided in an embodiment of this disclosure;
[0033] Figure 2This is a schematic diagram of a laminated body provided in an embodiment of the present disclosure;
[0034] Figure 3 This is one of the embodiments provided in this disclosure. Figure 2 A partial magnified structural diagram;
[0035] Figure 4 This is a schematic diagram of the structure of the first electrode sheet as viewed from the inside of the first current collector, provided by an embodiment of this disclosure;
[0036] Figure 5 This is a schematic diagram of the structure of the first electrode sheet as viewed from the outside of the first current collector, provided by an embodiment of this disclosure;
[0037] Figure 6 This is a schematic diagram of the structure of a composite sheet as viewed from the inside of the second current collector, provided in an embodiment of this disclosure;
[0038] Figure 7 This is a schematic diagram of the structure of a composite sheet as viewed from the outside of the second current collector, provided in an embodiment of this disclosure;
[0039] Figure 8 This is a schematic diagram of the installation structure between the core, plastic casing and rigid casing in a solid-state battery according to an embodiment of this disclosure;
[0040] Figure 9 This is a front view structural diagram of a solid-state battery provided in an embodiment of this disclosure;
[0041] Figure 10 This is a side view of a solid-state battery according to an embodiment of the present disclosure;
[0042] Figure 11 This is a top view schematic diagram of a solid-state battery provided in an embodiment of this disclosure.
[0043] Explanation of reference numerals in the attached figures
[0044] 1. Core; 1001. Beginning end; 1002. End; 001. Straight section; 002. Curled section;
[0045] 10. Laminated sheet; 101. First straight section; 102. Second straight section; 103. Curved section; 11. First electrode sheet; 111. First current collector; 112. First active material layer; 113. First tab; 1131. First ceramic edge; 20. Composite sheet; 201. Second ceramic edge; 12. Second electrode sheet; 121. Second current collector; 122. Second active material layer; 123. Second tab; 13. Solid electrolyte layer; 114. Green adhesive;
[0046] 2. Plastic shell;
[0047] 3. Rigid shell; 31. Annular frame; 32. Side wall. Detailed Implementation
[0048] To make the objectives, technical solutions, and advantages of this disclosure clearer, the embodiments of this disclosure will be described in further detail below with reference to the accompanying drawings.
[0049] This embodiment relates to a winding core, which is obtained by winding a laminated sheet 10. And as shown... Figure 1 As shown, the core includes a straight portion 001 and two curled portions 002 located on both sides of the straight portion 001.
[0050] The laminate 10 includes multiple first straight segments 101, multiple second straight segments 102, and multiple curled segments 103. (Reference) Figure 2 As shown, multiple first straight segments 101 and multiple second straight segments 102 are alternately connected to multiple curled segments 103 along the winding direction of the laminate 10.
[0051] refer to Figure 1 As shown, after the laminated sheet 10 is wound, multiple first straight segments 101 and multiple second straight segments 102 are stacked together to form a straight portion 001, and multiple curled segments 103 are respectively curled and stacked on one side of the straight portion 001 to form a curled portion 002.
[0052] For example, in Figure 2 In the process, the laminated sheet 10 can be wound clockwise from the first end 1001, gradually rolling the laminated sheet 10 outwards until it is as shown. Figure 1 As shown, the core has the first end 1001 located on the innermost side and the last end 1002 located on the outermost side.
[0053] Among them, Figure 2 In this context, the portion of the laminate 10 closest to the beginning 1001 can be the first straight segment 101, but in other possible examples, the portion of the laminate 10 closest to the beginning 1001 can also be the straight segment 102 or the curled segment 103.
[0054] Furthermore, at least a portion of the first flat segment 101 comprises an oxide solid electrolyte. This oxide solid electrolyte can be lithium lanthanum zirconate (LLZO), lithium aluminum titanium phosphate (LATP), lithium aluminum germanium phosphate (LAGP), or lithium lanthanum titanium oxide (LLTO), etc.
[0055] At least a portion of the second flat section 102 comprises at least one of a sulfide solid electrolyte and a halide solid electrolyte.
[0056] For example, a portion of the main components of the second flat section 102 may include a sulfide solid electrolyte.
[0057] For example, a portion of the main components of the second flat section 102 may include a halide solid electrolyte.
[0058] For example, a portion of the main components of the second straight section 102 may include a sulfide solid electrolyte and a halide solid electrolyte, and the mass ratio of the sulfide solid electrolyte to the halide solid electrolyte may be from 0.1:9.9 to 9.9:0.1. Preferably, the mass ratio of the sulfide solid electrolyte to the halide solid electrolyte may be from 5:5 to 9.8:0.2. For example, the mass ratio of the sulfide solid electrolyte to the halide solid electrolyte may be 5:5, 5.5:4.5, 6:4, 6.3:3.7, 7:3, 7.6:2.4, 8:2, 8.2:1.8, 9:1, 9.3:0.7, etc.
[0059] Among them, sulfide solid electrolytes can be Li2S-GeS2, Li2S-P2S5, or Li2S-SiS2, etc. Halide solid electrolytes include Li3InCl6, Li3ErCl6, Li3ScCl6, or Li3HoCl6, etc.
[0060] As described above, the main component of the first flat section 101 includes an oxide solid electrolyte, thus exhibiting high mechanical strength and a low expansion rate during charging and discharging, which is beneficial for reducing the capacity decay rate of the solid-state battery. The main component of the second flat section 102 includes at least one of a sulfide solid electrolyte and a halide solid electrolyte, enabling it to have high ionic conductivity. Therefore, the flat portion 001 formed by stacking multiple first flat sections 101 and multiple second flat sections 102 allows for a higher capacity of the solid-state battery and a lower capacity decay rate.
[0061] In some examples, due to the high expansion rates of sulfide solid electrolytes and halide solid electrolytes during charge and discharge, reference Figure 1 As shown, after the laminate 10 is wound, multiple first straight segments 101 and multiple second straight segments 102 can be alternately stacked together to form a straight portion 001. In this way, the two side surfaces of the second straight segments 102 in the stacking direction can be supported and restricted by the first straight segments 101 with higher mechanical strength, which helps to reduce the expansion rate of the second straight segments 102, thereby helping to further reduce the capacity decay rate of the solid-state battery.
[0062] For example, starting from the second straight segment from the first end 1001, the first straight segment 101 and the second straight segment 102 can be grouped in pairs, with multiple groups of first straight segments 101 and multiple groups of second straight segments 102 alternately distributed along the winding direction of the laminate 10. Furthermore, of the first and second straight segments starting from the first end 1001, one can be the first straight segment 101 and the other can be the second straight segment 102. Thus, in the straight portion 001, multiple first straight segments 101 and multiple second straight segments 102 can be alternately stacked.
[0063] Among them, Figure 1 In the above, the first straight segment starting from the beginning 1001 can be the first straight segment 101, but in other possible examples, the first straight segment starting from the beginning 1001 can be the second straight segment 102.
[0064] In some examples, the main components of the coiled segment 103 include at least one of a sulfide solid electrolyte and a polymer solid electrolyte. Because sulfide solid electrolytes and polymer solid electrolytes have good flexibility, they help to prevent problems such as cracking or peeling of the electrolyte coating on the coiled segment 103 during the winding process of the laminate 10.
[0065] For example, the main component of the coiled segment 103 may include a sulfide solid electrolyte.
[0066] For example, the main component of the coiled segment 103 may include a polymer solid electrolyte.
[0067] For example, the main components of the coiled segment 103 include a sulfide solid electrolyte and a polymer solid electrolyte, and the mass ratio of the sulfide solid electrolyte to the polymer solid electrolyte can be from 0.1:9.9 to 9.9:0.1. Preferably, the mass ratio of the sulfide solid electrolyte to the polymer solid electrolyte can be from 1:9 to 5:5. For example, the mass ratio of the sulfide solid electrolyte to the polymer solid electrolyte can be 1:9, 1.2:8.8, 2:8, 2.3:7.7, 3:7, 3.7:6.3, 4:6, 4.4:5.6, 5:5, etc.
[0068] The sulfide solid electrolyte can be Li2S-GeS2, Li2S-P2S5, or Li2S-SiS2, etc., while the polymer solid electrolyte can be polyethylene oxide (PEO), polyacrylonitrile (PAN), polyvinylidene fluoride (PVDF), polymethyl methacrylate (PMMA), polypropylene oxide (PPO), or polyvinylidene chloride (PVDC), etc.
[0069] In some examples, reference Figure 2 and combined Figure 3As shown, the laminate 10 is formed by stacking a first electrode sheet 11 and a composite sheet 20. The composite sheet 20 is formed by stacking two solid electrolyte layers 13 and a second electrode sheet 12 located between the two solid electrolyte layers 13. One of the first electrode sheet 11 and the other of the second electrode sheet 12 is a positive electrode sheet, and the other is a negative electrode sheet. For example, the first electrode sheet 11 can be a positive electrode sheet, and the second electrode sheet 12 can be a negative electrode sheet. However, it is also possible that the first electrode sheet 11 is a negative electrode sheet, and the second electrode sheet 12 is a positive electrode sheet.
[0070] refer to Figure 3 As shown, the first electrode sheet 11 includes a first current collector 111 and a first active material layer 112 coated on both sides of the first current collector 111. The second electrode sheet 12 may include a second current collector 121 and a second active material layer 122 coated on both sides of the second current collector 121.
[0071] In this embodiment, the first electrode sheet 11 is a positive electrode sheet, and the second electrode sheet 12 is a negative electrode sheet. The first current collector 111 can be an aluminum foil, and the components of the first active material layer 112 can include a positive active material, a solid electrolyte, a conductive agent, and a binder. The second current collector 121 can be a copper foil, and the second active material layer 122 can include a negative active material, a solid electrolyte, a conductive agent, and a binder. The solid electrolyte layer 13 can include a solid electrolyte and a binder.
[0072] The primary component of the first active material layer 112 located in the first straight section 101 may include an oxide solid electrolyte. The primary component of the first active material layer 112 located in the second straight section 102 may include at least one of a sulfide solid electrolyte and a halide solid electrolyte. The primary component of the first active material layer 112 located in the coiled section 103 may include at least one of a sulfide solid electrolyte and a polymer solid electrolyte.
[0073] The main component of the second active material layer 122 located in the first straight section 101 may include an oxide solid electrolyte. The main component of the second active material layer 122 located in the second straight section 102 may include at least one of a sulfide solid electrolyte and a halide solid electrolyte. The main component of the second active material layer 122 located in the coiled section 103 may include at least one of a sulfide solid electrolyte and a polymer solid electrolyte.
[0074] The main component of the solid electrolyte layer 13 located in the first straight section 101 may include an oxide solid electrolyte. The main component of the solid electrolyte layer 13 located in the second straight section 102 may include at least one of a sulfide solid electrolyte and a halide solid electrolyte. The main component of the solid electrolyte layer 13 located in the coiled section 103 may include at least one of a sulfide solid electrolyte and a polymer solid electrolyte.
[0075] For example, the solid electrolyte in the first straight section 101 of the first active material layer 112, the second active material layer 122, and the solid electrolyte layer 13 may all include an oxide solid electrolyte, and the solid electrolyte in the second straight section 102 may include at least one of a sulfide solid electrolyte and a halide solid electrolyte. The solid electrolyte in the coiled section 103 may include at least one of a sulfide solid electrolyte and a polymer solid electrolyte.
[0076] When the solid electrolyte in the second straight section 102 is a mixture of sulfide solid electrolyte and halide solid electrolyte, the mass ratio of the sulfide solid electrolyte to the halide solid electrolyte in the first active material layer 112, the second active material layer 122, and the solid electrolyte layer 13 can be from 0.1:9.9 to 9.9:0.1, preferably from 5:5 to 9.8:0.2. For example, the mass ratio of the sulfide solid electrolyte to the halide solid electrolyte in the second straight section 102 of the first active material layer 112, the second active material layer 122, and the solid electrolyte layer 13 can be 5:5, 5.5:4.5, 6:4, 6.3:3.7, 7:3, 7.6:2.4, 8:2, 8.2:1.8, 9:1, 9.3:0.7, etc.
[0077] When the solid electrolyte located in the coiled section 103 is a blend of sulfide solid electrolyte and polymer solid electrolyte, the mass ratio of the sulfide solid electrolyte to the polymer solid electrolyte can be from 0.1:9.9 to 9.9:0.1, preferably from 1:9 to 5:5. For example, the mass ratio of the sulfide solid electrolyte to the polymer solid electrolyte located in the coiled section 103 of the first active material layer 112, the second active material layer 122, and the solid electrolyte layer 13 can be 1:9, 1.2:8.8, 2:8, 2.3:7.7, 3:7, 3.7:6.3, 4:6, 4.4:5.6, 5:5, etc.
[0078] Furthermore, after the laminate 10 is wound, the areal density of the first active material layer 112 located in the curled portion 002 is 30%-100% of the areal density of the first active material layer 112 located in the straight portion 001, preferably 40%-85%. For example, after the laminate 10 is wound, the areal density of the first active material layer 112 located in the curled portion 002 can be 40%, 46%, 53%, 62%, 78%, 80%, 83%, etc., of the areal density of the first active material layer 112 located in the straight portion 001.
[0079] In this way, compared with the flat part 001, since the areal density of the first active material layer 112 and the second active material 122 of the curled part 002 is lower, on the one hand, the first active material layer 112 is not easy to peel off from the first current collector 111 during winding, the second active material 122 is not easy to peel off from the second current collector 121, and the first active material layer 112 and the second current collector 121 are not easy to be damaged. On the other hand, it can also reduce the degree of expansion, which is beneficial to reduce the rate of capacity decay of solid-state battery.
[0080] In some examples, the N / P ratio between the second electrode 12 and the first electrode 11 is 1.05-1.3. The N / P ratio is the ratio of the capacity of the negative electrode to the positive electrode coated with active material per unit area. For example, the N / P ratio between the second electrode 12 and the first electrode 11 can be 1.05, 1.06, 1.09, 1.12, 1.15, 1.19, 1.23, 1.26, 1.3, etc.
[0081] In some examples, the areal density of the first active material layer 112 located in the flat portion 001 can be 3 mg / cm³. 2 -30mg / cm 2 Preferably, it can be 4 mg / cm³. 2 -20mg / cm 2 For example, the areal density of the first active material layer 112 located in the straight section 001 can be 4.55 mg / cm³. 2 5mg / cm 2 7mg / cm 2 8mg / cm 2 10mg / cm 2 12mg / cm 2 15.3 mg / cm 2 16.9 mg / cm 2 18.8 mg / cm 2 19.2 mg / cm 2In this way, on the one hand, the areal density can be too low, which would reduce the battery capacity, and on the other hand, it can not be too high, which would reduce the mechanical stability and ionic conductivity of the solid electrolyte layer 13, thus helping to reduce the rate of capacity decay of the solid battery.
[0082] In some examples, after the laminate 10 is wound, the areal density of the solid electrolyte layer 13 located in the flat portion 001 is 1 mg / cm³. 2 -20mg / cm 2 For example, the areal density of the portion of the solid electrolyte layer 13 located in the flat section 001 can be 2 mg / cm³. 2 3.5 mg / cm 2 5mg / cm 2 6mg / cm 2 7mg / cm 2 8mg / cm 2 9.3 mg / cm 2 12.5 mg / cm 2 13.6 mg / cm 2 15.8 mg / cm 2 17.6 mg / cm 2 20mg / cm 2 wait.
[0083] When the areal density of the solid electrolyte layer 13 located in the flat section 001 is less than or equal to 5 mg / cm³ 2 When the solid electrolyte layer 13 located in the curled portion 002 has a surface density of 60%-95% of the surface density of the solid electrolyte layer 13 located in the flat portion 001, preferably 65%-85%. For example, the surface density of the solid electrolyte layer 13 located in the curled portion 002 can be 65%, 68%, 70%, 73%, 74%, 78%, 81%, 82%, 84%, etc., of the surface density of the solid electrolyte layer 13 located in the flat portion 001.
[0084] When the areal density of the solid electrolyte layer 13 located in the flat part 001 is greater than 5 mg / cm³ 2 When the solid electrolyte layer 13 located in the curled portion 002 has a surface density of 10%-95% of the surface density of the solid electrolyte layer 13 located in the flat portion 001, preferably 20%-70%. For example, the surface density of the solid electrolyte layer 13 located in the curled portion 002 can be 20%, 24%, 31%, 36%, 42%, 46%, 51%, 59%, 67%, 70%, etc., of the surface density of the solid electrolyte layer 13 located in the flat portion 001.
[0085] In this way, compared with the flat part 001, since the solid electrolyte layer 13 of the coiled part 002 has a lower surface density, on the one hand, the solid electrolyte layer 13 is less likely to separate from the first active material layer 112 and the second active material 122 during winding, and is less likely to be damaged. On the other hand, it can also reduce the degree of expansion, which is beneficial to reduce the rate of capacity decay of the solid battery.
[0086] In some examples, reference Figure 4 and Figure 5 As shown, green adhesive 114 can be provided at both ends of the two first active material layers 112 along the winding direction, and the two ends of the first active material layer 112 can be bonded to the first current collector 111 through the corresponding green adhesive 114. This helps to avoid problems such as burrs and wrinkles in the first active material layer 112.
[0087] In some examples, reference Figure 3 As shown, a plurality of first tabs 113 can extend from one side of the first current collector 111 along the width direction, and as... Figure 1 As shown, after the laminate 1 is wound, multiple first tabs 113 can be located on the same straight line, which facilitates the welding of multiple first tabs 113 together. In this way, multiple first tabs 113 can shorten the electron transport path, reduce internal resistance, and help improve the cycle life of solid-state batteries. It should be noted that the width direction is perpendicular to both the winding direction and the thickness direction.
[0088] In some examples, reference Figure 5 As shown, multiple second tabs 123 can extend from one side of the second current collector 121 along the width direction, and as... Figure 1 As shown, after the laminate 1 is wound, multiple second tabs 123 can be located on the same straight line, which facilitates the welding of multiple second tabs 123 together. In this way, multiple second tabs 123 can shorten the electron transport path, reduce internal resistance, and help improve the cycle life of solid-state batteries.
[0089] In some examples, reference Figure 3 As shown, the two sides of the root of the first electrode tab 113 are coated with a first ceramic edge 1131. This helps to prevent short circuits caused by contact between the first electrode plate 11 and the second electrode plate 12.
[0090] In some examples, the coating thickness of the first ceramic edge 1131 can be 4μm-6μm. For example, the coating thickness of the first ceramic edge 1131 can be 4μm, 4.2μm, 4.6μm, 5.1μm, 5.6μm, 5.9μm, 6μm, etc.
[0091] In some examples, the coating width of the first ceramic edge 1131 can be 2mm-7mm. For example, the coating width of the first ceramic edge 1131 can be 2mm, 2.5mm, 3mm, 3.6mm, 4.1mm, 4.6mm, 5.3mm, 5.6mm, 6.4mm, 7mm, etc.
[0092] In some examples, when the second electrode piece 12 is the negative electrode piece, the reference is... Figure 6 and Figure 7 and combined Figure 3 As shown, the solid electrolyte layer 13 has two second ceramic edges 201 on both sides of its surface facing away from the second active material layer 122 along the width direction. When the composite sheet 20 is stacked with the first electrode sheet 11, the first electrode sheet 11 can be located between the two second ceramic edges 201, and the two sides of the first electrode sheet 11 along the width direction can be in close contact with the two second ceramic edges 201 respectively.
[0093] In some examples, the thickness of the second ceramic edge 201 is approximately equal to the thickness of the first electrode sheet 11.
[0094] In some examples, the width of the second ceramic edge 201 can be 0.5 to 0.75 times the overhang of the second electrode sheet 12 relative to the first electrode sheet 11. Here, overhang refers to the portion of the negative electrode sheet that extends beyond the positive electrode sheet in both the length and width directions.
[0095] In some examples, the outermost layer of the core 1 is a first current collector 111 or a second current collector 112, which helps to prevent the first active material layer 112, the second active material layer 122, and the solid electrolyte layer 13 from falling off or being damaged. For example Figure 1 As shown, the outermost layer of the core 1 is a first current collector 111.
[0096] In some examples, the end of core 1 can be bonded to the corresponding position using green adhesive 114. This facilitates the fixation of core 1. For example... Figure 1 As shown, the end of the core 1 can be bonded to the corresponding position of the first current collector 111 by the green adhesive 114.
[0097] Secondly, refer to Figure 8 As shown, this embodiment also provides a solid-state battery, which includes any of the winding cores 1 in the first aspect.
[0098] The solid-state battery of this embodiment includes any of the winding cores 1 in the first aspect, and has all the beneficial technical effects of any embodiment of this disclosure.
[0099] In some examples, the solid-state battery also includes a plastic casing 2 that encloses the core 1. For example, the plastic casing 2 can be polyetheretherketone (PEEK), polyoxymethylene (POM / acetal), glass fiber reinforced polycarbonate, polyetherimide (PEI), epoxy composite materials, or polyamide fibers. Preferably, the material can be polyetheretherketone (PEEK), polyetherimide (PEI), or similar materials. Thus, the plastic casing 2, with its balanced insulation, thermal conductivity, malleability, mechanical strength, and light weight, can limit the expansion of the core 1. Furthermore, when the core 1 expands, the plastic casing 2 can adapt to the deformation, which helps to avoid damage to the core 1.
[0100] In some examples, the solid-state battery also includes a rigid housing 3 that encloses the core 1. The rigid housing 3 is not easily deformed and can effectively limit the expansion of the core 1.
[0101] In some examples, reference Figures 8 to 11 As shown, the rigid housing 3 includes an annular frame 31 and two side walls 32.
[0102] Among them, the annular frame 31 surrounds the core 1, and the annular frame 31 is made of nickel-plated steel.
[0103] Two sidewalls 32 are located on both sides of the core 1 along the stacking direction of the straight portion 001 of the core 1, and the outer edges of both sidewalls 32 are connected to the annular frame 31. The sidewalls 32 are made of aluminum. The annular frame 31 and the sidewalls 32 can be fixedly connected together by welding, bolts, or other methods.
[0104] In this way, the nickel-plated steel annular frame 31 has high mechanical strength and can effectively limit the curled part 12, which is prone to large expansion. For the flat part 11, which can expand to a smaller extent, the aluminum sidewall 32 can effectively limit the expansion and has a lower weight. This is beneficial to meeting the requirements of lightweighting.
[0105] In some examples, when the solid-state battery also includes a plastic casing 2, a rigid casing 3 encloses the plastic casing 2. In this way, the rigid casing 3 can avoid damaging the core 1 by enclosing the plastic casing 2, while also ensuring an effective restraint on the expansion of the core 1.
[0106] In some examples, when the solid-state battery includes a plurality of first tabs 113 and a plurality of second tabs 123, the plurality of first tabs 113 may be welded together and extend from the plastic housing 2 and the rigid housing 3, and the plurality of second tabs 123 may be welded together and extend from the plastic housing 2 and the rigid housing 3.
[0107] Thirdly, a battery pack is provided, comprising a solid-state battery according to any one of the second aspects. Thus, the battery pack possesses all the advantages of the solid-state batteries described above.
[0108] Fourthly, a vehicle is provided that includes the battery pack of the third aspect. Thus, the vehicle possesses all the advantages of the aforementioned battery pack. The vehicle can be an electric vehicle, a hybrid vehicle, or the like.
[0109] The specific embodiments of the present invention will now be described in more detail. While specific embodiments of the present invention are described below, it should be understood that the present invention can be implemented in various forms and should not be limited to the embodiments set forth herein. Where specific techniques or conditions are not specified in the embodiments, they are performed in accordance with the techniques or conditions described in the literature in the art or according to the product instructions. Reagents or instruments whose manufacturers are not specified are all conventional products that can be obtained commercially.
[0110] Example 1
[0111] Example 1 provides a solid-state battery, which includes a core 1, a plastic casing 2, and a rigid casing 3. The plastic casing 2 encloses the core 1, and the rigid casing 3 encloses the plastic casing 2.
[0112] The first current collector 111 of the core 1 is aluminum foil, and the second current collector 121 is copper foil.
[0113] The first active material layer 112 of the core 1 comprises the following components by mass percentage: 65% ternary cathode material (NCM811), 32.5% solid electrolyte, 1.5% conductive carbon black (SP), and 1% binder polyvinylidene fluoride (PVDF). The second active material layer 122 of the core 1 comprises the following components by mass percentage: 50% silicon carbide (SiC), 47.5% solid electrolyte, 1.5% conductive carbon black (SP), and 1% binder polyvinylidene fluoride (PVDF). The solid electrolyte layer 13 of the core 1 comprises the following components by mass percentage: 97% solid electrolyte and 3% binder polyvinylidene fluoride (PVDF).
[0114] The solid electrolyte in the first straight section 101 is an oxide solid electrolyte, lithium lanthanum zirconate (LLZO). The solid electrolyte in the second straight section 102 is a blend of sulfide solid electrolyte Li₂S—GeS₂ and halide solid electrolyte Li₃InCl₆, with a blending mass ratio of 9.7:0.3. The solid electrolyte in the coiled section 103 is a blend of sulfide solid electrolyte Li₂S—GeS₂ and polymer solid electrolyte polyethylene oxide (PEO), with a blending mass ratio of 1.5:8.5.
[0115] The areal density of the first active material layer 112 in both the first straight section 101 and the second straight section 102 is 12.2 mg / cm³. 2 The areal density of the first active material layer 112 in the curled section 103 is 46.1% of the areal density of the first active material layer 112 in the first straight section 101 and the second straight section 102, which is 5.625 mg / cm³. 2 .
[0116] The N / P ratio between the first electrode plate 11 and the second electrode plate 12 is 1.1.
[0117] The areal density of the solid electrolyte layer 13 in the first flat section 101 and the second flat section 102 is 3.2 mg / cm³. 2 The areal density of the solid electrolyte layer 13 in the curled section 103 is 66% of the areal density of the solid electrolyte layer 13 in the first straight section 101 and the second straight section 102, which is 2.112 mg / cm³. 2 .
[0118] The thickness of the 1311 coating on the first ceramic edge is 5μm and the width is 4mm.
[0119] The second ceramic edge 201 coating has a thickness of 5μm and a width of 4mm.
[0120] The annular frame 31 of the rigid shell 3 is made of nickel-plated steel with a thickness of 0.2 mm, and the sidewall 32 is made of aluminum plate with a thickness of 0.2 mm. The plastic shell 2 is made of polyetheretherketone (PEEK). The inner side of the plastic shell 2 is tightly fitted to the outer periphery of the isostatically pressed core 1, and the distance between the corresponding positions of the inner side of the plastic shell 2 and the isostatically pressed core 1 is 0.05 mm. The outer periphery of the plastic shell 2 is tightly fitted to the inner side of the rigid shell 3, and the distance between the corresponding positions of the inner side of the rigid shell 3 and the outer periphery of the plastic shell 2 is 0.05 mm. The rigid shell 3 is negatively charged.
[0121] Example 2
[0122] Example 2 provides a solid-state battery, which differs from Example 1 in that the material of the plastic casing 2 is different. Specifically, the plastic casing 2 in Example 2 is made of polyetherimide (PEI).
[0123] Example 3
[0124] Example 3 provides a solid-state battery, which differs from Example 1 in that the distance between the inner side of the plastic shell 2 and the corresponding position of the isostatically pressed core 1 is different. Specifically, the distance between the inner side of the plastic shell 2 and the corresponding position of the isostatically pressed core 1 is 0.01 mm.
[0125] Example 4
[0126] Example 4 provides a solid-state battery, which differs from Example 1 in that the distance between the inner side of the rigid shell 3 and the outer periphery of the plastic shell 2 is different. Specifically, the distance between the inner side of the rigid shell 3 and the outer periphery of the plastic shell 2 is 0.01 mm.
[0127] Comparative Example 1
[0128] Comparative Example 1 provides a solid-state battery, which differs from Example 1 in that the distance between the inner side of the plastic shell 2 and the corresponding position of the isostatically pressed core 1 is different. Specifically, the distance between the inner side of the plastic shell 2 and the corresponding position of the isostatically pressed core 1 is 0.2 mm.
[0129] Comparative Example 2
[0130] Comparative Example 2 provides a solid-state battery, which differs from Example 1 in that the distance between the corresponding positions of the inner side of the rigid shell 3 and the outer side of the plastic shell 2 is different. Specifically, the distance between the corresponding positions of the inner side of the rigid shell 3 and the outer side of the plastic shell 2 is 0.2 mm.
[0131] Comparative Example 3
[0132] Comparative Example 3 provides a solid-state battery that differs from Example 1 in that the areal density of the first active material layer 112 in the curled section 103 is different. Specifically, the areal density of the first active material layer 112 in the curled section 103 is 30% of the areal density of the first active material layer 112 in the first straight section 101 and the second straight section 102, i.e., 3.66 mg / cm³. 2 .
[0133] Comparative Example 4
[0134] Comparative Example 4 provides a solid-state battery that differs from Example 1 in that the areal density of the first active material layer 112 in the curled section 103 is different. Specifically, the areal density of the first active material layer 112 in the curled section 103 is 100% of the areal density of the first active material layer 112 in the first straight section 101 and the second straight section 102, i.e., 12.2 mg / cm³. 2 .
[0135] Comparative Example 5
[0136] Comparative Example 5 provides a solid-state battery, which differs from Example 1 in that the solid electrolyte located in the first flat section 101 in the first active material layer 11 and the second active material layer 12 is different. Specifically, the solid electrolyte located in the first flat section 101 in the first active material layer 11 and the second active material layer 12 is a polymer solid electrolyte.
[0137] Comparative Example 6
[0138] Comparative Example 6 provides a solid-state battery that differs from Example 1 in that the mass ratio of the sulfide solid electrolyte Li2S-GeS2 and the polymer solid electrolyte polyethylene oxide (PEO) in the coiled section 103 of the first active material layer 11 and the second active material layer 12 is different. Specifically, the mass ratio of the sulfide solid electrolyte Li2S-GeS2 and the polymer solid electrolyte polyethylene oxide (PEO) in the coiled section 103 of the first active material layer 11 and the second active material layer 12 is 0.1:9.9.
[0139] Comparative Example 7
[0140] Comparative Example 7 provides a solid-state battery that differs from Example 1 in that the mass ratio of the sulfide solid electrolyte Li2S-GeS2 and the polymer solid electrolyte polyethylene oxide (PEO) in the coiled section 103 of the first active material layer 11 and the second active material layer 12 is different. Specifically, the mass ratio of the sulfide solid electrolyte Li2S-GeS2 and the polymer solid electrolyte polyethylene oxide (PEO) in the coiled section 103 of the first active material layer 11 and the second active material layer 12 is 9.9:0.1.
[0141] Comparative Example 8
[0142] Comparative Example 8 provides a solid-state battery, which differs from Example 1 in that the areal density of the solid electrolyte layer 13 in the curled section 103 is different. Specifically, the areal density of the solid electrolyte layer 13 in the curled section 103 is 60% of the areal density of the solid electrolyte layer 13 in the first flat section 101 and the second flat section 102, i.e., 1.92 mg / cm³. 2 .
[0143] Comparative Example 9
[0144] Comparative Example 9 provides a solid-state battery that differs from Example 1 in that the areal density of the solid electrolyte layer 13 in the curled section 103 is different. Specifically, the areal density of the solid electrolyte layer 13 in the curled section 103 is 95% of the areal density of the solid electrolyte layer 13 in the first flat section 101 and the second flat section 102, i.e., 3.04 mg / cm³. 2 .
[0145] Comparative Example 10
[0146] Comparative Example 10 provides a solid-state battery that differs from Example 1 in that the mass ratio of the sulfide solid electrolyte Li2S-GeS2 and the polymer solid electrolyte polyethylene oxide (PEO) in the coiled section 103 of the solid electrolyte layer 13 is different. Specifically, the mass ratio of the sulfide solid electrolyte Li2S-GeS2 and the polymer solid electrolyte polyethylene oxide (PEO) in the coiled section 103 of the solid electrolyte layer 13 is 0.1:9.9.
[0147] Comparative Example 11
[0148] Comparative Example 11 provides a solid-state battery that differs from Example 1 in that the mass ratio of the sulfide solid electrolyte Li2S-GeS2 and the polymer solid electrolyte polyethylene oxide (PEO) in the coiled section 103 of the solid electrolyte layer 13 is different. Specifically, the mass ratio of the sulfide solid electrolyte Li2S-GeS2 and the polymer solid electrolyte polyethylene oxide (PEO) in the coiled section 103 of the solid electrolyte layer 13 is 9.9:0.1.
[0149] Test case
[0150] Using test examples, the solid-state batteries provided in Examples 1 to 4 and Comparative Examples 1 to 11 were tested for energy density, full-charge internal resistance, 1C / 0.1C rate performance, 1C / 1C cycle performance at room temperature, and the full-charge thickness expansion rate of the bare cells before and after cycling. The test results are shown in Table 1.
[0151] Table 1. Cell performance test data for the examples and comparative examples.
[0152]
[0153] According to the comparison of the data of Examples 1, 3 and 4 with Comparative Examples 1 and 2 in Table 1, it can be seen that the smaller the distance between the core 1 and the plastic shell 2 and the smaller the distance between the plastic shell 2 and the rigid shell 3, the better the room temperature cycling performance of the battery cell and the lower the full-charge thickness expansion rate of the battery cell before and after cycling.
[0154] According to the comparison of the data of Example 1 and Comparative Example 3 in Table 1, the energy density of the battery cell is higher when the areal density of the first active material layer 112 in the curled section 103 is 40%-85% of the areal density of the first active material layer 112 in the first straight section 101 and the second straight section 102.
[0155] According to the comparison of the data of Example 1 and Comparative Example 4 in Table 1, the cell has better room temperature cycling performance when the areal density of the first active material layer 112 in the curled section 103 is 40%-85% of the areal density of the first active material layer 112 in the first straight section 101 and the second straight section 102.
[0156] According to the comparison of the data of Example 1 and Comparative Example 5 in Table 1, when the solid electrolyte located in the first straight section 101 in the first active material layer 11 and the second active material layer 12 is an oxide solid electrolyte, the cell has better room temperature cycling performance.
[0157] Based on the comparison of data from Example 1 with Comparative Examples 6 and 7 in Table 1, it can be seen that when the mass ratio of the sulfide solid electrolyte to the polymer solid electrolyte in the coiled section 103 of the first active material layer 11 and the second active material layer 12 is between 1:9 and 5:5, the cell exhibits lower full-charge internal resistance, better rate performance, and better room-temperature cycling performance.
[0158] According to the comparison of the data of Example 1 with Comparative Examples 8 and 9 in Table 1, it can be seen that when the areal density of the solid electrolyte layer 13 in the first straight section 101 and the second straight section 102 is less than or equal to 5 mg / cm³, the areal density of the solid electrolyte layer 13 is less than or equal to 5 mg / cm³. 2 When the areal density of the solid electrolyte layer 13 in the curled section 103 is 65%-85% of the areal density of the solid electrolyte layer 13 in the first straight section 101 and the second straight section 102, the cell has good room temperature cycling performance.
[0159] According to the comparison of the data of Example 1 with Comparative Examples 10 and 11 in Table 1, it can be seen that when the mass ratio of the sulfide solid electrolyte and the polymer solid electrolyte polyethylene oxide compound located in the coiled section 103 in the solid electrolyte layer 13 is 1:9 to 5:5, the cell has a low full-charge internal resistance, good rate performance, and good room temperature cycling performance.
[0160] Therefore, as shown in Table 1, the main component of the first flat section (101) includes an oxide solid electrolyte, which can have high mechanical strength and low expansion rate during charging and discharging, thus helping to reduce the capacity decay rate of the solid-state battery. The main component of the second flat section (102) includes at least one of a sulfide solid electrolyte and a halide solid electrolyte, which can have high ionic conductivity. Therefore, the flat section (001) formed by stacking multiple first flat sections (101) and multiple second flat sections (102) can improve the battery capacity of the solid-state battery and reduce the capacity decay rate of the solid-state battery.
[0161] It should be noted that, in the description of this application, unless otherwise expressly specified and limited, the terms "installation," "connection," and "linking" should be interpreted broadly. For example, they can refer to a fixed connection, a detachable connection, or an integral connection; they can refer to a mechanical connection; they can refer to a direct connection or an indirect connection through an intermediate medium; they can refer to the internal communication of two components or the interaction between two components. Those skilled in the art can understand the specific meaning of the above terms in this application according to the specific circumstances.
[0162] Furthermore, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. Therefore, features defined as "first" or "second" may explicitly or implicitly include one or more features. In the description of this application, "multiple" means two or more, unless otherwise explicitly specified.
[0163] In the description of this specification, the references to the terms "certain embodiments", "one embodiment", "some embodiments", "illustrative embodiment", "example", "specific example", or "some examples" refer to specific features, structures, materials, or characteristics described in connection with the embodiments or examples that are included in at least one embodiment or example of this application.
[0164] The above are merely embodiments of this application and are not intended to limit this application. Any modifications, equivalent substitutions, improvements, etc., made within the principles of this application should be included within the protection scope of this application.
Claims
1. A type of winding core, characterized in that, The core is formed by winding a laminated sheet (10) and includes a straight portion (001) and two curled portions (002) located on both sides of the straight portion (001). The laminate (10) includes a plurality of first straight segments (101), a plurality of second straight segments (102), and a plurality of curled segments (103). Multiple first straight segments (101) and multiple second straight segments (102) are alternately connected with multiple curled segments (103) along the winding direction of the laminate (10). After the laminate (10) is wound, multiple first straight segments (101) and multiple second straight segments (102) are stacked together to form the straight portion (001), and multiple curled segments (103) are respectively curled and stacked on the side corresponding to the straight portion (001) to form the curled portion (002). At least a portion of the first flat segment (101) comprises an oxide solid electrolyte as its main component; At least a portion of the main components of the second flat segment (102) includes at least one of a sulfide solid electrolyte and a halide solid electrolyte.
2. The winding core according to claim 1, characterized in that, After the stacked sheet (10) is wound, a plurality of first straight segments (101) and a plurality of second straight segments (102) are alternately stacked together to form the straight portion (001).
3. The winding core according to claim 1, characterized in that, The main components of the coiled segment (103) include at least one of a sulfide solid electrolyte and a polymer solid electrolyte.
4. The winding core according to any one of claims 1 to 3, characterized in that, The laminate (10) is obtained by stacking a first electrode sheet (11) and a composite sheet (20), wherein the composite sheet (20) is obtained by stacking two solid electrolyte layers (13) and a second electrode sheet (12) located between the two solid electrolyte layers (13); The first electrode sheet (11) includes a first current collector (111) and a first active material layer (112) coated on both sides of the first current collector (111). The main component of the first active material layer (112) located in the first straight section (101) includes an oxide solid electrolyte, and the main component of the first active material layer (112) located in the second straight section (102) includes at least one of a sulfide solid electrolyte and a halide solid electrolyte. After the laminate (10) is wound, the areal density of the first active material layer (112) located in the curled portion (002) is 30%-100% of the areal density of the first active material layer (112) located in the straight portion (001).
5. The winding core according to claim 4, characterized in that, After the laminate (10) is wound, the areal density of the first active material layer (112) located in the curled portion (002) is 40%-85% of the areal density of the first active material layer (112) located in the straight portion (001).
6. The winding core according to claim 4, characterized in that, After the laminate (10) is wound, the areal density of the solid electrolyte layer (13) located in the flat portion (001) is 1 mg / cm³. 2 -20mg / cm 2 ; When the areal density of the solid electrolyte layer (13) located in the flat portion (001) is less than or equal to 5 mg / cm³ 2 At that time, the areal density of the solid electrolyte layer (13) located in the curled portion (002) is 60%-95% of the areal density of the solid electrolyte layer (13) located in the straight portion (001); When the areal density of the solid electrolyte layer (13) located in the flat portion (001) is greater than 5 mg / cm³ 2 At that time, the areal density of the solid electrolyte layer (13) located in the curled portion (002) is 10%-95% of the areal density of the solid electrolyte layer (13) located in the straight portion (001).
7. The winding core according to claim 6, characterized in that, When the areal density of the solid electrolyte layer (13) located in the flat portion (001) is less than or equal to 5 mg / cm³ 2 At that time, the areal density of the solid electrolyte layer (13) located in the curled portion (002) is 65%-85% of the areal density of the solid electrolyte layer (13) located in the straight portion (001); When the areal density of the solid electrolyte layer (13) located in the flat portion (001) is greater than 5 mg / cm³ 2 At that time, the areal density of the solid electrolyte layer (13) located in the curled portion (002) is 20%-70% of the areal density of the solid electrolyte layer (13) located in the straight portion (001).
8. A solid-state battery, characterized in that, The solid-state battery comprises the winding core (1) as described in any one of claims 1 to 7.
9. The solid-state battery according to claim 8, characterized in that, The solid-state battery also includes a plastic casing (2) that encloses the core (1).
10. The solid-state battery according to claim 8 or 9, characterized in that, The solid-state battery also includes a rigid housing (3) that encloses the core (1).
11. The solid-state battery according to claim 10, characterized in that, The rigid shell (3) includes an annular frame (31) and two side walls (32). The annular frame (31) surrounds the core (1), and the annular frame (31) is made of nickel-plated steel; The two sidewalls (32) are located on both sides of the core (1) along the stacking direction of the straight portion (001) of the core (1), and the outer edges of the two sidewalls (32) are connected to the annular frame (31). The sidewalls (32) are made of aluminum.
12. The solid-state battery according to claim 10, characterized in that, When the solid-state battery also includes a plastic casing (2), the rigid casing (3) encloses the plastic casing (2).
13. A battery pack, characterized in that, The battery pack includes the solid-state battery as described in any one of claims 8 to 12.
14. A vehicle, characterized in that, The vehicle includes the battery pack as described in claim 13.
Citation Information
Patent Citations
Solid state battery and solid state battery manufacturing method
CN111864274A
Composite solid electrolyte, preparation method thereof, battery and electric equipment
CN118472354A